User-centred design of a digital advisory service: enhancing public agricultural extension for sustainable intensification in Tanzania - Ortíz Crespo, Berta; Steinke, Jonathan; Quirós, Carlos F.; Gevel, Jeske M.J, van de; Daudi, Happy; Mgimiloko, Majuto Gaspar; Etten, Jacob van (Informa UK Limited, 2021)
Sustainable intensification (SI) is promoted as a rural development paradigm for sub-Saharan Africa. Achieving SI requires smallholder farmers to have access to information that is context-specific, increases their decision-making capacities, and adapts to changing environments. Current extension services often struggle to address these needs. New mobile phone-based services can help. In order to enhance the public extension service in Tanzania, we created a digital service that addresses smallholder farmers’ different information needs for implementing SI. Using a co-design methodology – User-Centered Design – we elicited feedback from farmers and extension agents in Tanzania to create a new digital information service, called Ushauri. This automated hotline gives farmers access to a set of pre-recorded messages. Additionally, farmers can ask questions in a mailbox. Extension agents then listen to these questions through an online platform, where they record and send replies via automated push-calls. A test with 97 farmers in Tanzania showed that farmers actively engaged with the service to access agricultural advice. Extension agents were able to answer questions with reduced workload compared to conventional communication channels. This study illustrates how User-Centered Design can be used to develop information services for complex and resource-restricted smallholder farming contexts.